1983
DOI: 10.2307/1422574
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hand-Eye Dominance in Relation to Verbal Self-Regulation of Motor Behavior

Abstract: The development of the relation between hand-eye dominance and verbal self-control of motor behavior was examined with 4- and 5-year-olds. Performances of subjects falling into either crossed or consistent hand-eye dominance categories were compared on a two-choice button-pushing task. Children performed this with their dominant hand in one of two conditions: verbalizing and not verbalizing their button-pushing activity. Results showed that crossed hand-eye dominant children gave significantly poorer performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Crossed eye/hand laterality has been related to alcohol dependence (Yüksel et al., ) and other mental disorders such as other addictions or schizophrenia (Dane et al., ; Giotakos, ), and a poorer outcome in neuropsychological test conditions in early childhood (Nagae, ). Conversely, other studies suggested that crossed patterns of lateralization also exert protective effects such as a better clinical outcome in patients with schizophrenia and a lower prevalence in children with learning disabilities (Connolly, ; Gorynia et al., ; Liu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Crossed eye/hand laterality has been related to alcohol dependence (Yüksel et al., ) and other mental disorders such as other addictions or schizophrenia (Dane et al., ; Giotakos, ), and a poorer outcome in neuropsychological test conditions in early childhood (Nagae, ). Conversely, other studies suggested that crossed patterns of lateralization also exert protective effects such as a better clinical outcome in patients with schizophrenia and a lower prevalence in children with learning disabilities (Connolly, ; Gorynia et al., ; Liu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have linked C-HELPs with specific cognitive disorders. For example, Porac & Coren (1976) found that the C-HELP was more prevalent in individuals manifesting a variety of behavioral disorders, and Nagae (1983) showed that C-HELP children performed significantly worse at verbal self-regulation of motor behavior, supporting the view that the functions of cerebral hemispheres in C-HELP children were more immature and linked with learning disabilities. However, a meta-analysis by Bourassa, MacManus & Bryden (1996) with 54,087 participants from 47 studies on hand-eye laterality did not find enough evidence to associate hand-eye laterality with learning and indicated the necessity of conducting more research in the field.…”
Section: Introductionmentioning
confidence: 91%
“…A response of right was assigned a score of + 1, a response of left was assigned a score of −1, and an either response was assigned a 0. This method of scoring incorporates not only the direction but also the strength of the handedness (Nagae, 1983). The mean degree of the hand dominance of subjects used in this experiment was as follows: right-handed males = 10.67 ( SD = 1.14), left-handed males = −8.67 ( SD = 1.84), right-handed females = 11.33 ( SD = 0.94), and left-handed females = −8.42 ( SD = 1.75).…”
Section: Methodsmentioning
confidence: 99%